The effect of memorable tourism experience on group tourists’ satisfaction: The moderating role of visit frequency - Hoàng Văn Hảo (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
The main purpose of this study is to examine the influence of each component of the Memorable Tourism Experience (MTE) on group tourists’ satisfaction. In addition to the direct influence, the number of destination visits is considered as a moderator in these relationships. Beach and island tourism is chosen as the context of the study. Data from the survey (N = 317) was analyzed using SmartPLS 4.0 software. Structural model analysis was used to analyze the direct and moderate effects in the research model. The research results showed that four components of MTE including hedonism (β = 0.136), novelty (β = 0.148), refreshment (β = 0.213) and involvement (β = 0.234) had an impact on tourists’ satisfaction; while the effects of three remaining (meaningfulness, knowledge and local culture) were not statistically significant. In addition, the visit frequency plays a moderating role in the impact of hedonism and refreshment. The results provide suggestions for destination managers and travel business managers in developing personalized tourism products based on visit frequency and MTE.